The Pengaruh Peran Pemimpin, Budaya Organisasi, Motivasi Intrinsik Terhadap Disiplin Kerja Pegawai Di Politeknik Pembangunan Pertanian Yogyakarta Magelang - Yolan, Marselina; Septyarini, Epsilandri; Purnamarini, Tri Ratna (Indonesian Journal Publisher, 2025)
This study aims to analyze the influence of leadership roles, organizational culture, and intrinsic motivation on employee work discipline at the Yogyakarta Magelang Agricultural Development Polytechnic. Work discipline is a crucial factor in supporting organizational effectiveness, thus it is essential to examine its relationship with both internal organizational and individual factors. This research employed a quantitative approach, with data collected through questionnaires distributed to 70 employees of the institution. The data were analyzed using the Statistical Package for the Social Sciences (SPSS) version 25. The results indicate that the leadership role has a significant positive effect on employee work discipline. Furthermore, a strong organizational culture is proven to positively contribute to improving employee discipline. Intrinsic motivation also shows a significant positive influence on the level of work discipline, suggesting that the higher the employee's intrinsic motivation, the better their discipline performance. Simultaneously, the leadership role, organizational culture, and intrinsic motivation have a positive and significant combined effect on work discipline. These findings highlight the importance of strengthening leadership, fostering a constructive organizational culture, and enhancing intrinsic motivation in order to improve employee work discipline within vocational higher education institutions.